A miniature shielded‐loop active H‐field probe design with high spatial resolution for near‐field measurement. Issue 1 (18th October 2021) - Yi, Zhiqiang; Tang, Sha; Liu, Jiesheng; Shao, Weiheng; Shao, E; He, Xiao; Fang, Wenxiao; Gao, Yang
Abstract: A miniature practical active magnetic field (H‐field) probe with 0.5 mm × 0.15 mm loop size is designed for electromagnetic interference analysis in electronic systems from 150 kHz to 12 GHz. This probe is fabricated in a four‐layer printed circuit board using high‐performance and low‐loss Rogers material (RO4350B). A low noise amplifier with 14 dB‐gain is applied to amplify the radio frequency detect signal. The spatial resolution of the proposed probe is verified under the microstrip with different widths (1.55 and 0.24 mm). In addition, the verification results indicate that the proposed small loop active shielded H‐field probe can obtain the better spatial resolution of 422 μm with liftoff = 100 μm. Regarding to the sensitivity of the probe, the proposed probe realizes 16.7 dB μA at 3 GHz with the liftoff = 100 μm. compared with other commercial probes and a reference probe, the proposed probe has better spatial resolution at 150 kHz–12 GHz and sensitivity at 1.5–12 GHz.